Quantification of carotenoid and flavonoid components in brans of some thai black rice cultivars using supercritical fluid extraction and high-performance liquid chromatography-mass spectrometry - Muntana Nakornriab (2018)
A method employing supercritical fluid extraction (SFE) followed by high-performance liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS) was developed and used for quantification of the antioxidants in groups of carotenoids and flavonoids in the bran of four Thai black rice cultivars: Kao Hom Nin BD, Kao Hom Nin BT, Kao Hom Nin BT no. 3 and 1000-11-2-26. Trans-β-carotene, quercetin and isorhamnetin were identified in the crude yellow extracts obtained from SFE using liquid chromatography- tandem mass spectrometry (LC-MS/MS). Their contents in the black rice bran samples were determined using LC-ESI-MS operated in the selected ion monitoring (SIM) mode. The response of the mass spectrometric detection in the SIM mode was linear, within the range of 1.00-40.00 μg/mL (r2 = 0.9997), 0.25-2.00 μg/mL (r2 = 0.9987) and 0.25-2.00 μg/mL (r 2 = 0.9982); the limit of detection was at 0.10, 0.15 and 0.15 μg/mL, and the limit of quantitation was 0.80 g of rice bran for trans-β-carotene and 0.60 g of rice bran for both quercetin and isorhamnetin. Method precisions in terms of intraday and inter-day coefficients of variation were under 3.67% (relative standard deviation). The accuracy of the method estimated by determination of known concentrations of trans-β-carotene in the certified reference material, Standard Reference Material 3276, was found to range from 92 to 101%. Trans-β-carotene, quercetin and isorhamnetin were present in the bran of all black rice cultivars within the range of 33.60-41, 1.08-2.85 and 0.05-0.83 μg/g, respectively. © 2008, The Author(s).